Structural control and functionalization of thermoresponsive nanogels: turning cross-linking points into anchoring groups - Wolfel Sánchez, Alexis (2023)
Advancements in nanogel (NG) applications require precise control over their size, structure, and functionalization. However, synthesis methods have limitations that hinder the incorporation of some functional groups and hamper the architectural control over NGs. In this work, we developed a facile post-synthesis reaction strategy to modify the structure and functionalization of thermoresponsive NGs. Specifically, we studied the incorporation of a cleavable crosslinker, (+)-N,N′-diallyltartardiamide (DAT), in the synthesis of poly(N-isopropylacrylamide) (p-NIPAm), poly(N-isopropylmethacrylamide) (p-NIPMAm), and p-NIPAm-co-NIPMAm-based NGs. The efficient cleavage of DAT-crosslinks by sodium periodate enables control over the crosslinking degree and architecture of the NGs. This cleavage reaction also introduces alpha-oxoaldehydes (glyoxylic groups), which can be used for subsequent bio-conjugation under mild conditions. The incorporation of DAT-crosslinks in the NG architecture is governed by the reactivity of monomers and crosslinkers, as well as the initiation method used. Consequently, the structural changes caused by the cleavage of DAT-crosslinks depend on the composition and synthesis parameters, providing a valuable tool for fine-tuning drug delivery nanodevices in a post-synthetic step. As proof of concept, we demonstrated that the cleavage of DAT-crosslinks increased the loading efficiency of bovine serum albumin, a macromolecular drug surrogate. Additionally, we used the obtained alpha-oxoaldehydes to covalently link doxorubicin (DOXO) through hydrazone bonds, introducing pH-selective drug release.